PENERAPAN ALGORITMA C4.5 PADA KLASIFIKASI POTENSI SISWA DROP OUT - Muhamad Muhamad; Agus Perdana Windarto; Suhada Suhada (STMIK Budi Darma, 2019)
Students are one of the substances that need to be considered in relation to the world of education today. The difficulty of getting students makes the school have to optimize the learning system and infrastructure as well to attract the interest of new students and also make students who have gone to school not drop out or drop out. One of the factors contributing to the large number of students dropping out is because of the lack of policies and actions from the education institutions to keep their students from dropping out. The purpose of this study was to classify potentially dropout students and not have the potential to drop out with the C4.5 algorithm as a reference in making policies and actions to reduce the number of students dropping out. The classification results of the C4.5 algorithm are evaluated and validated with RapidMinerStudio to determine the accuracy of the C4.5 Algorithm in classifying potential dropouts.Keywords: Student dropout, Classification, C4.5 Algorithm